Fastening materials
The fastening member, composed of an aluminum alloy with specific elemental ratios and microstructural features, addresses the issue of low stress relaxation resistance in conventional fastening members, delivering enhanced relaxation resistance and reliable fastening performance.
Patent Information
- Application Number
- JP2021574633
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-01-15
AI Technical Summary
Conventional aluminum alloys used in fastening members exhibit low resistance to loosening due to stress relaxation.
A fastening member made from an aluminum alloy with a specific composition and microstructural characteristics, including a mass ratio of 0.6% to 1.4% silicon, 0.5% to 5.0% copper, 0.3% to 1.1% manganese, 0.5% to 1.3% magnesium, and 0.01% to 0.8% zinc, with an average crystal grain size of 4 μm to 50 μm and an average crystal orientation difference of 1.5 degrees or less.
The fastening member achieves excellent relaxation resistance, maintaining axial force after thermal exposure, thereby ensuring reliable fastening performance.
Smart Images

Figure 0007650827000002 
Figure 0007650827000003 
Figure 0007650827000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a fastening member. [Background technology]
[0002] Conventionally, weight reduction of various parts has been pursued as one of the measures to improve fuel efficiency of automobiles. For example, aluminum alloys have been used instead of cast iron as the material for engine blocks, and magnesium alloys have been used instead of steel as the material for engine covers and oil pans.
[0003] As a means of reducing weight, there has been a growing trend to use aluminum alloys and magnesium alloys as materials for fastening members that fasten parts together. In particular, aluminum alloy bolts have a small difference in linear expansion coefficient with the aluminum and magnesium alloys that make up various parts, and are less susceptible to galvanic corrosion, so they are suitable for reducing weight because they can ensure fastening reliability even if the screw holes in the parts are made shallow or the bolt diameter is made small.
[0004] The aluminum alloys used for fastening members are 6000 series aluminum alloys, which are suitable for strength, heat resistance, corrosion resistance, and workability. In order to further improve the properties, adjustment of the components and the use of 7000 series aluminum alloys, which have higher strength than the 6000 series, are being considered (see, for example, Patent Documents 1 and 2). In Patent Document 1, the properties are improved by including a specified amount of strontium (Sr). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-104123 A [Patent Document 2] JP 2017-202497 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, conventional aluminum alloys have a problem in that they have low resistance to loosening due to stress relaxation (relaxation resistance).
[0007] The present invention has been made in view of the above, and has an object to provide a fastening member that is excellent in relaxation resistance. [Means for solving the problem]
[0008] In order to solve the above-mentioned problems and achieve the object, the fastening member of the present invention is characterized in that it contains, by mass, 0.6% or more and 1.4% or less of silicon, 0.5% or more and 5.0% or less of copper, 0.3% or more and 1.1% or less of manganese, 0.5% or more and 1.3% or less of magnesium, and 0.01% or more and 0.8% or less of zinc, with the remainder being aluminum and unavoidable impurities, and has a circle-equivalent average crystal grain size in a region from the surface to a depth of 200 μm of 4 μm or more and 50 μm or less.
[0009] Moreover, in the fastening member according to the present invention, the average crystal orientation difference in a region from the surface to a depth of 200 μm is 1.5 degrees or less.
[0010] In addition, the fastening member according to the present invention is characterized in that in the above invention, the ratio of the proportional limit to the tensile strength is 0.6 or more. Effect of the Invention
[0011] According to the present invention, a fastening member having excellent relaxation resistance can be provided. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a side view showing the configuration of a fastening member according to a first embodiment of the present invention. [Diagram 2]FIG. 2 is a flowchart illustrating the method for manufacturing the fastening member according to the first embodiment of the present invention. [Diagram 3] FIG. 3 is a plan view showing the configuration of a fastening member according to the second embodiment of the present invention. [Figure 4] FIG. 4 is a diagram showing a crystal grain map in the thread root of the fastening member according to Example 1 of the present invention. [Diagram 5] FIG. 5 is a diagram showing a crystal grain map in the thread root of the fastening member according to Example 2 of the present invention. [Figure 6] FIG. 6 is a diagram showing a crystal grain map in the thread root of the fastening member according to Example 3 of the present invention. [Figure 7] FIG. 7 is a diagram showing a crystal grain map in the thread root of the fastening member according to Example 4 of the present invention. [Figure 8] FIG. 8 is a diagram showing a crystal grain map in the thread root of the fastening member according to Comparative Example 1 of the present invention. [Figure 9] FIG. 9 is a diagram showing a crystal grain map in the thread root of a fastening member according to Comparative Example 2 of the present invention. [Figure 10] FIG. 10 is a diagram showing a crystal grain map in the thread root of a fastening member according to Comparative Example 3 of the present invention. [Figure 11] FIG. 11 is a diagram showing a crystal grain map in the thread root of a fastening member according to Comparative Example 4 of the present invention. [Figure 12] FIG. 12 is a diagram showing a crystal orientation difference map in the thread groove of the fastening member according to Example 1 of the present invention. [Figure 13] FIG. 13 is a diagram showing a crystal orientation difference map in the thread groove of the fastening member according to Example 2 of the present invention. [Figure 14] FIG. 14 is a diagram showing a crystal orientation difference map in the thread groove of the fastening member according to Comparative Example 1 of the present invention. [Figure 15] FIG. 15 is a diagram showing a crystal orientation difference map in the thread groove of a fastening member according to Comparative Example 2 of the present invention. [Figure 16] FIG. 16 is a diagram for explaining the timing of measuring the axial force in the relaxation resistance test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "embodiment") will be described with reference to the attached drawings. Note that the drawings are schematic, and the relationship between the thickness and width of each part, the thickness ratio of each part, etc. may differ from the actual ones, and the drawings may include parts with different dimensional relationships and ratios.
[0014] (Embodiment 1) FIG. 1 is a side view showing the configuration of a fastening member according to a first embodiment of the present invention. The fastening member 1 shown in FIG. 1 is a bolt (a type of male screw) made of an aluminum (Al) alloy. The fastening member 1 includes a cylindrical shaft portion 2, a head portion 3 provided at one end of the shaft portion 2 in the axial direction (left-right direction in FIG. 1), and a neck portion 4 forming a boundary between the shaft portion 2 and the head portion 3. The shaft portion 2 has a threaded portion 22 having a thread 21 formed on its surface. Note that the shape of the head portion 3 (hexagonal trim type) is merely an example, and other shapes (hexagonal flange type, pan type, dish type, truss type, flat type, etc.) may be used. Note that a thread groove 23 is formed between adjacent threads 21 in the axial direction of the shaft portion 2. The head portion 3 is not necessarily required, and a stud bolt without a head (for example, JIS standard: JIS B 1173) may be used.
[0015] The fastening member 1 is made of an aluminum alloy containing silicon (Si), copper (Cu), manganese (Mn), magnesium (Mg) and zinc (Zn), with the balance being aluminum (Al) and unavoidable impurities. The aluminum alloy according to the present embodiment is an alloy having a composition equivalent to the aluminum alloy having the alloy number A6056, or an alloy having a composition equivalent to the aluminum alloy A6056 with an increased amount of Cu. Specifically, the aluminum alloy contains, by mass ratio, 0.6% to 1.4% Si, 0.5% to 5.0% Cu, 0.3% to 1.1% Mn, 0.5% to 1.3% Mg, and 0.01% to 0.8% Zn. The aluminum alloy may also contain a combination of zirconium (Zr) and titanium (Ti) at 0.2% or less. The Cu content (standard value) of the A6056 aluminum alloy is 0.5% to 1.1%. In the following description, the content refers to the content ratio in mass ratio.In the following description, the content refers to the content ratio in mass ratio.
[0016] In the aluminum alloy according to the first embodiment, Si precipitates as Mg2Si by aging treatment, and the precipitation of Mg2Si can increase the strength. If the Si content exceeds 1.4%, the elongation of the alloy is reduced. If the Si content is less than 0.6%, the strength improvement effect of the Mg2Si precipitates is insufficient.
[0017] Cu precipitates CuAl2 and Al2CuMg by aging treatment, and these precipitates can increase strength. In particular, if the Cu content is 1.5% or more and 4.0% or less, the amount of these precipitates can be further increased, and strength can be further improved. On the other hand, if the Cu content exceeds 5.0%, the corrosion resistance, stress corrosion cracking resistance, and elongation of the alloy are reduced. Also, if the Cu content is less than 0.5%, the strength improvement effect of these precipitates is insufficient.
[0018] Mn is an element that exhibits solid solution strengthening. In addition, Al-Mn-Si precipitates are formed by aging treatment, which can increase strength. Here, if the Mn content exceeds 1.1%, the elongation of the alloy is reduced. Also, if the Mn content is less than 0.3%, the strength-improving effect of these precipitates is insufficient.
[0019] Mg can increase strength by precipitating Mg2Si during aging treatment. If the Mg content exceeds 1.3%, the elongation decreases. If the Mg content is less than 0.5%, the strength improvement effect of the Mg2Si precipitates is insufficient.
[0020] Zn increases strength by precipitating MgZn2 during aging treatment. If the Zn content exceeds 0.8%, the corrosion resistance, stress corrosion cracking resistance, and elongation of the alloy are reduced. If the Zn content is less than 0.01%, the strength improvement effect of these precipitates is insufficient.
[0021] The fastening member 1 has a circle-equivalent average crystal grain size of 4 μm or more and 50 μm or less in a region from the surface of the thread groove 23 to a depth of 200 μm. Here, the depth from the thread groove 23 is the distance from the surface of the thread groove 23 toward the central axis of the shaft portion 2 and perpendicular to this central axis. The circle-equivalent average crystal grain size here is the diameter of the circle. If the circle-equivalent average crystal grain size is less than 4 μm, grain boundary sliding is likely to occur, which is thought to reduce the relaxation resistance. On the other hand, if the circle-equivalent average crystal grain size exceeds 50 μm, ductility is reduced and the possibility of cracks occurring during heading and rolling processes increases.
[0022] Furthermore, the fastening member 1 has a KAM (Kernel Average Misorientation) value, which indicates the average crystal orientation difference in the region from the surface to a depth of 200 μm in the thread valley 23, of 1.5 degrees or less. If the KAM value exceeds 1.5 degrees, there is a lot of residual strain, which is thought to reduce relaxation resistance.
[0023] Moreover, the fastening member 1 has a tensile strength of 400 MPa or more. If the tensile strength is less than 400 MPa, the fastening member will need to be made larger in size in order to maintain the load resistance (reduced axial force resistance) during fastening, which impairs weight reduction.
[0024] Furthermore, the fastening member 1 has a 0.2% yield strength, which is the stress at which the permanent strain remaining after unloading is 0.2%, of 370 MPa or more. If the 0.2% yield strength is less than 370 MPa, the load during elastic region fastening is small, and compensating for this requires an increase in the size of the fastening member, which impairs the weight reduction.
[0025] Furthermore, the ratio of the proportional limit to the tensile strength of the fastening member 1 (proportional limit / tensile strength) is 0.6 or more, and preferably 0.7 or more. If the ratio (proportional limit / tensile strength) is less than 0.6, the load during fastening in the elastic region is relatively small, and compensating for this requires an increase in the size of the fastening member, which impairs weight reduction. The proportional limit is the maximum stress at which Hooke's law holds true in the stress-strain curve.
[0026] The fastening member 1 is formed by subjecting a bar-shaped member made of the above-mentioned aluminum alloy to processing, etc. Fig. 2 is a flow chart illustrating a method for manufacturing the fastening member according to the first embodiment of the present invention.
[0027] First, the rod-shaped member described above is pressed (step S101). In this pressing process, the rod-shaped member is sandwiched between dies and pressurized. By pressing, for example, one end of the rod-shaped member is crushed to produce a first molded product having a shaft portion 2 excluding a threaded portion 22, a head portion 3, and a neck portion 4.
[0028] Thereafter, the first molded product formed by pressing is rolled (step S102). In this rolling process, the first molded product is sandwiched between dies having projections and recesses corresponding to the threads and pressurized, and while rotating the first molded product, one die is moved relative to the other die to form the threads 21 on the shaft portion 2. A threaded portion 22 is formed on the shaft portion 2 by the rolling process.
[0029] After the rolling process, the second formed product having the threaded portion 22 formed therein is subjected to a heat treatment (step S103). In the heat treatment, the second formed product is treated at a high temperature to be solutionized (solution treatment), and then is subjected to an aging treatment. The set temperature in the solution treatment is preferably set to 500°C to 570°C, and the set temperature in the aging treatment is preferably set to 140°C to 200°C.
[0030] The fastening member 1 having the above-mentioned properties can be obtained by producing the fastening member 1 according to the above-mentioned flow. Conventionally, it is common to carry out the heat treatment in step S103 before the rolling treatment in step S102.
[0031] According to the embodiment 1 of the present invention described above, a fastening member with excellent relaxation resistance can be obtained by manufacturing a fastening member 1 using an aluminum alloy containing, by mass, 0.6% or more and 1.4% or less of silicon, 0.5% or more and 5.0% or less of copper, 0.3% or more and 1.1% or less of manganese, 0.5% or more and 1.3% or less of magnesium, and 0.01% or more and 0.8% or less of zinc, with the remainder being aluminum and unavoidable impurities, and performing a rolling process and then a heat treatment.
[0032] (Embodiment 2) Fig. 3 is a plan view showing the configuration of a fastening member according to embodiment 2 of the present invention. The fastening member 5 shown in Fig. 3 is a nut (a type of female thread) made of the above-mentioned aluminum alloy. The fastening member 5 is hollow and cylindrical, with a thread 52 formed on the inner surface of a hole 51 formed in the center. Note that the shape of the fastening member 5 shown in Fig. 3 (hexagonal nut) is merely one example, and it is also possible to realize it as a nut having another shape (flanged nut, cap nut, high nut, etc.).
[0033] The fastening member 5 is formed of the above-mentioned aluminum alloy and has a ring shape. The fastening member 5 is produced from a rod-shaped member made of the above-mentioned aluminum alloy in the same manner as in the first embodiment. For example, after rolling the threads 52, a heat treatment is performed.
[0034] According to the above-described embodiment 2 of the present invention, a fastening member 5 is manufactured using an aluminum alloy containing, by mass, 0.6% or more and 1.4% or less of silicon, 0.5% or more and 5.0% or less of copper, 0.3% or more and 1.1% or less of manganese, 0.5% or more and 1.3% or less of magnesium, and 0.01% or more and 0.8% or less of zinc, with the remainder being aluminum and unavoidable impurities, by performing a rolling process and then a heat treatment, a fastening member with excellent relaxation resistance can be obtained.
[0035] Although the embodiments of the present invention have been described above, the present invention should not be limited to the above-mentioned embodiments 1 and 2. For example, the fastening member according to the present invention can be realized as a machine screw or a tapping screw, which is a male screw other than a bolt. EXAMPLES
[0036] Examples of the aluminum alloy according to the present invention will be described below, but the present invention is not limited to these examples.
[0037] Example 1 A bolt (corresponding to fastening member 1) was produced by rolling and then heat treating a rod-shaped member of A6056 aluminum alloy according to the flow chart shown in FIG. 2. The bolt produced in this embodiment has a thread nominal of M8 and a pitch of 1.25. The average grain size and average crystal orientation difference (KAM value) were obtained for each depth of the thread valley using the electron backscatter diffraction (EBSD) method for some of the bolts. In addition, a tensile test was performed on the bolt to obtain the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The average grain size and average crystal orientation difference are values in the region from the bolt surface to depths of 100, 200, and 400 μm. The results are shown in Table 1. [Table 1]
[0038] Example 2 A bolt was produced by processing a rod-shaped A6056 aluminum alloy with a Cu content of 2.04% according to the flow chart shown in Figure 2. The average grain size and average crystal orientation difference (KAM value) were determined for each depth of the thread groove using the EBSD method for some of the bolts. In addition, a tensile test was performed on the bolt to determine the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The results are shown in Table 1.
[0039] Example 3 A bolt was fabricated by processing a rod-shaped member of A6056 aluminum alloy with the following composition: Si 0.92%, Fe 0.24, Cu 2.90%, Mn 0.65%, Mg 0.89%, and Zr+Ti 0.17% according to the flow chart shown in Figure 2. The average grain size and average crystal orientation difference (KAM value) were obtained for each depth of the thread groove by EBSD method for some of the bolts. In addition, tensile tests were performed on the bolts to obtain the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The results are shown in Table 1.
[0040] Example 4 A bolt was fabricated by processing a rod-shaped member of A6056 aluminum alloy with a composition of 0.92% Si, 3.94% Cu, 0.69% Mn, 0.88% Mg, and 0.17% Zr+Ti according to the flow chart shown in Figure 2. The average grain size and average crystal orientation difference (KAM value) were determined for each depth of the thread groove using the EBSD method for some of the bolts. In addition, a tensile test was performed on the bolt to determine the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The results are shown in Table 1.
[0041] Comparative Example 1 Bolts were produced from rod-shaped A6056 aluminum alloy members by switching the order of the rolling process in step S102 and the heat treatment in step S103 in the flow chart shown in Figure 2. The average grain size and average crystal orientation difference (KAM value) were determined for each depth of the thread groove using the EBSD method for some of these bolts. Tensile tests were also conducted on the bolts to determine the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The results are shown in Table 1.
[0042] Comparative Example 2 A bolt was produced by using a rod-shaped member of A6056 aluminum alloy with a Cu content of 2.04% and by switching the order of the rolling process in step S102 and the heat treatment in step S103 in the flow chart shown in Figure 2. The average grain size and average crystal orientation difference (KAM value) were determined for each depth of the thread groove using the EBSD method for some of the bolts. In addition, a tensile test was performed on the bolt to determine the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The results are shown in Table 1.
[0043] Comparative Example 3 A rod-shaped member having an A6056 aluminum alloy composition with a Si content of 0.92%, Fe content of 0.24, Cu content of 2.90%, Mn content of 0.65%, Mg content of 0.89%, and Zr+Ti content of 0.17% was used to manufacture a bolt by switching the order of the rolling process in step S102 and the heat treatment in step S103 in the flow chart shown in FIG. 2. The average grain size and average crystal orientation difference (KAM value) were obtained for each depth of the thread groove by the EBSD method for some of the bolts. In addition, a tensile test was performed on the bolt to obtain the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The results are shown in Table 1.
[0044] Comparative Example 4 A rod-shaped member having an A6056 aluminum alloy composition with a Si content of 0.92%, a Cu content of 3.94%, a Mn content of 0.69%, a Mg content of 0.88%, and a Zr+Ti content of 0.17% was used to manufacture a bolt by switching the order of the rolling process in step S102 and the heat treatment in step S103 in the flow chart shown in FIG. 2. The average grain size and average crystal orientation difference (KAM value) were obtained for each depth of the thread groove by the EBSD method for some of the bolts. In addition, a tensile test was performed on the bolt to obtain the tensile strength, 0.2% proof stress, and proportional limit / tensile strength. The results are shown in Table 1.
[0045] [Average grain size] FIG. 4 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Example 1 of the present invention. FIG. 5 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Example 2 of the present invention. FIG. 6 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Example 3 of the present invention. FIG. 7 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Example 4 of the present invention. FIG. 8 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Comparative Example 1 of the present invention. FIG. 9 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Comparative Example 2 of the present invention. FIG. 10 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Comparative Example 3 of the present invention. FIG. 11 is a diagram showing a crystal grain map in the thread groove of the fastening member according to Comparative Example 4 of the present invention. FIGS. 4 to 11 correspond to a part of a cross section including the deepest part of the thread groove (corresponding to the thread groove 23) of the manufactured bolt. The boundary line (black line) shown in the figure indicates a grain boundary with an orientation difference of 5° or more, and the grain surrounded by this boundary line is regarded as one crystal grain. The color shading in the figure is given according to the orientation in which the crystal grains are oriented. In Examples 1 to 4 and Comparative Examples 1 to 4, the average grain size was calculated as the distance from the deepest part of the thread groove (e.g., position P0 shown in FIG. 4), toward the central axis of the bolt shaft (corresponding to shaft 2) and in the direction perpendicular to this central axis, from the surface to 100 μm, 200 μm, and 400 μm. As can be seen from the results shown in Table 1 and from FIGS. 4 to 11, at each depth, the average grain size of the bolts (Examples 1 to 4) manufactured by rolling and heat treatment is larger than the average grain size of the bolts (Comparative Examples 1 to 4) manufactured by heat treatment and rolling. Also, when Example 1 is compared with Examples 2 to 4, it is found that the average grain size is larger in the composition with a higher Cu content.
[0046] [Average crystal orientation difference] FIG. 12 is a diagram showing a crystal orientation difference map in the thread valley of a fastening member according to Example 1 of the present invention. FIG. 13 is a diagram showing a crystal orientation difference map in the thread valley of a fastening member according to Example 2 of the present invention. FIG. 14 is a diagram showing a crystal orientation difference map in the thread valley of a fastening member according to Comparative Example 1 of the present invention. FIG. 15 is a diagram showing a crystal orientation difference map in the thread valley of a fastening member according to Comparative Example 2 of the present invention. FIGS. 12 to 15 correspond to a partial cross section including the deepest part of the thread valley (corresponding to thread valley 23) of the manufactured bolt. For the average crystal orientation difference (KAM value), the average of the orientation differences between all measurement points adjacent to the measurement point with a diameter of about 0.7 μm was calculated in each region from the surface to depths of 100 μm, 200 μm, and 400 μm. As can be seen from the results shown in Table 1 and from Figures 12 to 15, at each depth, the average crystal orientation difference of the bolts produced by rolling and heat treatment (Examples 1 and 2) is smaller than the average crystal orientation difference of the bolts produced by heat treatment and rolling (Comparative Examples 1 and 2).
[0047] [Tensile strength, 0.2% yield strength, and proportional limit / tensile strength] The tensile strength and 0.2% proof stress shown in Table 1 are the average values obtained from 10 measurements. The minimum and maximum values are shown in parentheses at the bottom. The proportional limit is the stress (load) when the relationship between load and stroke deviates from a straight line. If the proportional limit / tensile strength is 0.6 or more, the load during fastening in the elastic region can be relatively increased, making it possible to reduce the size of the fastening components, which in turn promotes weight reduction in the fastening components.
[0048] [Relaxation resistance] The bolt was fastened to the workpiece at room temperature, heated at 120°C for 20 hours, and then cooled to room temperature, and the axial force after heating was measured. FIG. 16 is a diagram for explaining the measurement timing of the axial force in the relaxation resistance test. In FIG. 16, the time change of the axial force is shown by a solid line F1, and the time change of the temperature is shown by a broken line T1. The temperature t0 is room temperature. In the relaxation resistance test, the axial force before heating (point Q1) and the axial force after heating (point Q2) were compared. It can be said that the smaller the change between the axial force before heating (point Q1) and the axial force after heating (point Q2) is, the more relaxation resistance the bolt has. The axial force before heating was set to 12.5 kN, which corresponds to the plastic region fastening of the A6056 aluminum alloy under the fastening conditions. The axial forces after heating of the bolts according to Examples 1 and 2 were 9.0 kN and 9.8 kN, while the axial forces after heating of the bolts according to Comparative Examples 1 and 2 were 8.2 kN and 8.8 kN. From these results, it is evident that, as in Examples 1 and 2, the case where heat treatment is performed after rolling provides superior relaxation resistance.
[0049] In this manner, the present invention may include various embodiments not described here, and various design modifications may be made without departing from the technical idea specified by the scope of the claims. [Industrial Applicability]
[0050] As described above, the fastening member according to the present invention is suitable for obtaining a fastening member having excellent relaxation resistance. [Explanation of symbols]
[0051] 1, 5 Fastening members 2 Shaft section 3 head 4 Neck 21, 52 threads 22 Threaded section 23 Screw Valley 51 holes
Claims
1. The alloy contains, by mass ratio, 0.6% or more and 1.4% or less of silicon, more than 1.1% or more and 5.0% or less of copper, 0.3% or more and 1.1% or less of manganese, 0.5% or more and 1.3% or less of magnesium, and 0.01% or more and 0.8% or less of zinc, with the balance being aluminum and inevitable impurities; The circle-equivalent average crystal grain size in the region from the surface to a depth of 200 μm is 4 μm or more and 50 μm or less. A fastening member characterized by:
2. The average crystal orientation difference in the region from the surface to a depth of 200 μm is 1.5 degrees or less. The fastening member according to claim 1 .
3. The ratio of the proportional limit to the tensile strength is 0.6 or more. The fastening member according to claim 1 or 2.
4. The copper content by mass is 1.5% or more and 4.0% or less, The fastening member according to claim 1 .
5. The circle-equivalent average crystal grain size in the region from the surface to a depth of 200 μm is 9 μm or more and 50 μm or less. The fastening member according to claim 4 .
Citation Information
Patent Citations
Preparation process of high-performance refined grain aluminum alloy wires and bars applied to aluminum bolts
CN104451478A
High-strength aluminum alloy wire and rod material excellent in softening resistance and method of manufacturing the same
JP2010189750A
Aluminum alloy wire rod material for high-strength bolt having excellent formability, method for producing the same, high-strength flange bolt and method for producing the same
JP2011001602A
Aluminum alloy wire for bolt, the bolt and methods for manufacturing the same
JP2013104123A
Manufacturing method of high strength aluminum alloy bolt
JP2017202497A